ANALYSIS CORRELATION DURATION OF USE WITH RISK OF INCREASED BLOOD PRESURE ON THE ACCEPTORS INJECTABLE CONTRACEPTIVE DEPO MEDROXYPROGESTERON ACETATE (DMPA) : A RETROSPECTIVE COHORT STUDY - Sekar Muktiyani; Nurmainah Nurmainah (Universitas Muhammadiyah Magelang, 2020)
Depo Medroxyprogesterone Acetate (DMPA) is a method of family planning program. DMPA is preferred because of its economical, practical, and effective in preventing pregnancy. Long-term use DMPA is suspected to be a risk of an increase in blood pressure. The purpose of this study was to analyze the correlation between duration of use with risk of hypertension in the DMPA acceptor at Perumnas II Pontianak Public Health Care. The research method was observational analytic with a retrospective cohort design. The population of the study is the new DMPA acceptor January-June 2018. This period is the index date for the use of DMPA or the date of the first use of DMPA by acceptors. The acceptor is followed by using DMPA for one year or more until the end of the 30 June 2019 study through its medical record data. Samples that met the inclusion and exclusion criteria were 81 acceptors. The results showed that acceptors with a duration of use of DMPA for more than 12 months had more risk of hypertension (66.7%) than acceptors with a duration of use for less than 12 months (38.5%). Chi-square analysis showed a significant correlation between the duration of use of DMPA and the risk of hypertension (p-value = 0.011, RR = 1.733 CI 95% = 1.104 - 2.72 in DMPA acceptor at Perumnas II Pontianak Public Health Care. The study concludes that there is a correlation between duration of use and risk of hypertension.